Detection of methadone and buprenorphine in urine samples from inmates of German prisons - Franchetti, Giorgia; Thierauf-Emberger, Annette; Franz, Anette; Thoma, Vanessa; Auwärter, Volker; Huppertz, Laura M. (Frontiers in Psychiatry, 2023)
Non-prescribed use of opioid substitution drugs is a serious public health problem, involving general population as well as peculiar populations such as prisoners. The estimation of the prevalence of opioid substitution drug misuse in prisoners is crucial to suggest strategies to counter this phenomenon and reduce the associated morbidity and mortality. The present study aimed to provide an objective estimation of the prevalence of illicit use of methadone and buprenorphine in two German prisons. Urine samples were collected from inmates of Freiburg and Offenburg prisons at random times and tested for the detection of methadone and buprenorphine and their metabolites. Analyses were performed by a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. In total 678 inmates participated in this study. The participation rate was about 60 % of all permanent inmates. Of the 675 samples suitable for the analysis, 70 samples (10.4 %) tested positive for methadone, 70 samples (10.4 %) for buprenorphine, and 4 samples (0.6 %) for both drugs. At least 100 samples (14,8 %) were not associated with reported prescribed-opioid substitution treatment (OST). Buprenorphine was the most common illicitly used drug. In one of the prisons, buprenorphine was brought in from the outside. The present cross-sectional experimental study was able to provide reliable information regarding the illicit use of opioid substitution drugs in prisons.